Cigarette Smoke Increases Endothelial CXCL16-Leukocyte CXCR6 Adhesion In Vitro and In Vivo. Potential Consequences in Chronic Obstructive Pulmonary Disease - Marques, Patrice; Collado, Aida; Escudero, Paula; Rius, Cristina; González, Cruz; Servera, Emilio; Piqueras, Laura; Sanz, Maria-Jesus (Frontiers in Immunology, 2017)
Cardiovascular disease (CVD) is a major co-morbidity in chronic obstructive pulmonary disease (COPD). Although the mechanism of its development remains largely unknown, it appears to be associated with cigarette consumption and reduced lung function. Therefore, the aim of this study was to investigate the potential link between water-soluble cigarette smoke extract (CSE)-induced endothelial dysfunction and the function of CXCL16/CXCR6 axis on the initial attachment of leukocytes, in addition to its possible impact on COPD-associated systemic inflammation. To do this, we employed several experimental approaches, including RNA silencing and flow cytometry analysis, the dynamic flow chamber technique, and intravital microscopy in the cremasteric arterioles of animals exposed to CS. CSE induced arterial CXCL16 expression, leading to increased platelet-leukocyte and mononuclear cell adhesiveness. CSE-induced CXCL16 expression was dependent on Nox5 expression and subsequent RhoA/p38-MAPK/NFκB activation. Flow cytometry analysis revealed that COPD patients (n=35) presented greater numbers of activated circulating platelets (PAC-1+ and P-selectin+) expressing CXCL16 and CXCR6 as compared with age-matched controls (n=17), with a higher number of CXCR6+-platelets in the smoking COPD group than in ex-smokers. This correlated with enhanced circulating CXCR6+-platelet-leukocyte aggregates in COPD patients. The increase in circulating numbers of CXCR6-expressing platelets and mononuclear cells resulted in enhanced platelet-leukocyte and leukocyte adhesiveness to CSE-stimulated arterial endothelium, which was greater than that found in age-matched controls and was partly dependent on endothelial CXCL16 up-regulation. Furthermore, cigarette smoke exposure provoked CXCL16-dependent leukocyte-arteriolar adhesion in cremasteric arterioles, which was significantly reduced in animals with a nonfunctional CXCR6 receptor. In conclusion, we provide the first evidence that increased numbers of CXCR6-expressing circulating platelets and mononuclear leukocytes from patients with COPD might be a marker of systemic inflammation with potential consequences in CVD development. Accordingly, CXCL16/CXCR6 axis blockade might constitute a new therapeutic approach for decreasing the risk of CVD in COPD patients.